2013
DOI: 10.4049/jimmunol.1300033
|View full text |Cite
|
Sign up to set email alerts
|

Invariant NKT Cells Induce Plasmacytoid Dendritic Cell (DC) Cross-Talk with Conventional DCs for Efficient Memory CD8+ T Cell Induction

Abstract: A key goal of vaccine immunotherapy is the generation of long-term memory CD8+ T cells capable of mediating immune surveillance. We discovered a novel intercellular pathway governing the development of potent memory CD8+ T cell responses against cell-associated Ags that is mediated through cross-presentation by XCR1+ dendritic cells (DCs). Generation of CD8+ memory T cells against tumor cells pulsed with an invariant NKT cell ligand depended on cross-talk between XCR1+ and plasmacytoid DCs that was regulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 54 publications
3
42
0
Order By: Relevance
“…It was shown that NKT cells can interact via OX40/OX40L with pDCs, which then contribute to the activation of conventional DCs for T cell priming (33,34). Because pDCs are a major producer of type I IFN (35), we assessed whether this cytokine contributed to the NKT cell-mediated conditioning observed in the previous experiments.…”
Section: Activated Nkt Cells Condition Different DC Subsets To Responmentioning
confidence: 98%
“…It was shown that NKT cells can interact via OX40/OX40L with pDCs, which then contribute to the activation of conventional DCs for T cell priming (33,34). Because pDCs are a major producer of type I IFN (35), we assessed whether this cytokine contributed to the NKT cell-mediated conditioning observed in the previous experiments.…”
Section: Activated Nkt Cells Condition Different DC Subsets To Responmentioning
confidence: 98%
“…(B) The absolute numbers of three MDSC subsets in the spleen from mice groups described in (A) were quantified after gating based on the expression levels of Gr1 and CD11b (n D 4-6, mean § SEM; *p < 0.05 for non-vs. anti-NK1.1). (C) NK cells were directly isolated from spleen of Rag1 ¡/¡ mice using anti-DX5 Ab-conjugated bead were cocultured with CD11b C Gr1 C MDSCs at a 1:1 ratio for 6 h. CD107 expression was analyzed using Alexa488-CD107a and IFNg production by intracellular staining as previously described 53 . (n D 4, mean § SEM; IFNg; *p < 0.05 for -MDSC vs. CMDSC in R2, CD107a; *p < 0.05 -MDSC vs. CMDSC in R1, R2, and R3) (D) NK cell cytotoxicity against each MDSC subset was determined as described in Methods (n D 4, mean § SEM; *p < 0.05 for Ly6G hi Ly6C med vs. Ly6G med Ly6C hi , and Ly6G hi Ly6C med vs. Ly6G med Ly6C med ).…”
Section: E995541-4mentioning
confidence: 99%
“…Using two different tumor models, our data reveal that a-GalCer/ Ag codelivery to CD8a + DCs triggers antitumor responses, in prophylactic and/or therapeutic settings. Of interest, Shimizu and colleagues (22,23) showed that inoculation of irradiated tumor cells previously loaded with a-GalCer promotes antitumor immunity through Ag cross-presentation and CTL responses. In this setting, dying tumor cells are selectively taken up by CD8a + DCs, and the subsequent cross-presentation of a-GalCer to NKT cells and tumor Ags to CD8 + T cells leads to strong and long-lasting antitumor responses (22).…”
Section: Nps Incorporating A-galcer and Ag Protect Against Tumor Devementioning
confidence: 99%
“…Of interest, Shimizu and colleagues (22,23) showed that inoculation of irradiated tumor cells previously loaded with a-GalCer promotes antitumor immunity through Ag cross-presentation and CTL responses. In this setting, dying tumor cells are selectively taken up by CD8a + DCs, and the subsequent cross-presentation of a-GalCer to NKT cells and tumor Ags to CD8 + T cells leads to strong and long-lasting antitumor responses (22). Using a different strategy (DC targeting by means of a synthetic vector), our data are in line with the concept that having both tumor Ag and a-GalCer on the same cell resulted in more efficient cross-presentation of Ag to CD8 + T cells.…”
Section: Nps Incorporating A-galcer and Ag Protect Against Tumor Devementioning
confidence: 99%
See 1 more Smart Citation